Comparison of Primary Simple Closure and Limberg Flap Technique in Pilonidal Sinus - Hafiza Kiran Saleem Butt; Aamna Nazir; Muhammad Atif Khan; Muhammad Idrees Anwar; Hira Waris; Shahzaib Maqbool (Journal of Rawalpindi Medical College)
Introduction